History and Nature of Science enriched Problem-Based Learning on the origins of biodiversity and of continents and oceans - Cristina Sousa (Multidisciplinary Journal for Education, Social and Technological Sciences)
The episode of the History of Science (HOS) on the theory of continental drift proposed by Alfred Wegener has been considered an excellent example for teaching students aspects of Nature of Science (NOS) and the relation of Science with social and tecnological contexts. We implemented a NOS and HOS-enriched Problem-Based Learning environment at the middle (year 7 of the Portuguese National Curriculum) and secondary level (year 10) for teaching the origins of biodiversity and of continents and oceans (mobilism).